Beyond Green: Human–environment geographies for the 'new' century. Issue 1 (March 2022) - Head, Lesley
The disciplinary heritage of examining human–environment relationships continues to be vital but needs continual updating. In the Australian context, four threads of work can make key contributions in the next few decades: (1) recognising the depth of colonial heritage in 20th-century environmental thought, (2) supporting new Indigenous Geographies, (3) articulating environmental imaginaries beyond the settler-Indigenous binary and (4) responding to precarity and volatility with new ecologies. These threads each have distinct research trajectories – in terms of both their heritage in Geography and their development this century. They nevertheless have in common significant potential to help the discipline address the central shared challenge of contemporary life: facing climate change with commitments to justice. I consider wider implications, including three risks we need to be alert to. One risk is eco-fascism. Another is the re-naturalisation of environmental change as climate change impacts are exacerbated. The third is the amount of energy that needs to go into analysing and negotiating our volatile institutional contexts, potentially at the expense of what we have hitherto understood as core scholarly business.